Magnitude, number and school mathematics - Norvaiša, Rimas (Lietuvos matematikos rinkinys, 2021)
Definitions of concepts of magnitude and number used in academic mathematics are not suitable for school mathematics for reasons of their cognitive complexity. We discuss possible ways to treat magnitudes and numbers in school mathematics based on mathematical reasoning.
Keywords: content of school mathematics; magnitude; number; number line; measurement